Bonding inspection using ultrasonic methods - Cheng, Xu (2015)
The purpose of this project was to apply the ultrasonic Time-of-Flight Diffraction technique to inspect and characterize the bonding condition between two metal blocks. Two aluminium block was chosen to be bonded together using epoxy adhesive and a few teflon fragments were put inside the bonding to form defects artificially. By connecting two wedge transducers to a handyscope, a simple TOFD apparatus with A-scan output was created to be used to conduct some experiments. Multi-group experiments were conducted, including checking the functionality of the device, testing the actual compression wave propagation speed in the specimen, TOFD inspection over the interated part and bonding area of the specimen. The results shown that the equipment were working well and the compression wave speed was close to the theoretical value. However, the signals acquired were not good as expected in terms of those TOFD inspection. The problem encountered was that there was no such significant pulse signal generated by compression wave which was expected to be used for signal analysis. Furthermore, for the experiments conducted over the bonded part, the signal got was just at the same level as the noise signal. The reasons for the failure in getting a good result as expected were complicated. Limitation of centre frequency for probe and the poor singal processing equipment were the two major causes. Inappropriate choice of bonding material and method also had a adverse effect on the experimental results. Even so, this project was a good pilot in applying theoretical method in practice, the work done in the project was a good reference for further study. In order to make full use of the TOFD mecthod, improvement in both equipment and the design of experiment should be done for future work.